For god, king and country: cult and territoriality in the Iron Age Levant. (2nd September 2022) - Hogue, Timothy
Abstract : In the 9th century BC, Levantine polities performatively expressed territoriality by strategically utilizing the spatial discourse of royal monuments. Specifically, Levantine rulers erected complementary monuments in both their core cities and frontier cities to transmit a central praxis and perspective to the periphery. This practice drew on earlier Levantine traditions of using monuments to demarcate ceremonial theatres that functioned as zones for political transformation. Most importantly, these 9th century monuments departed from earlier traditions by distributing the presence of both the king and his patron deity to multiple locations within his claimed territory. They thus created relationships between the denizens of diverse settlements and the king and his deity. By creating a shared political and religious experience, the monuments performatively brought forth concepts of a territorial polity centred on a single king, deity and capital city. This allowed these kings to express sovereignty over entire regions as opposed to collections of individual settlements.